The Effect of Training, Work Discipline and Incentives on Employee Performance of PT. Pamapersada Nusantara - Alfatih, Muhammad Haidar; Djazuli, Abid; Choiriyah, Choiriyah; Agusria, Lesi (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2024)
PT.I Pamapersadai Nusantara’si performance is still in below target due to their low quality of work results in in terms of production achievements caused by inappropriate work implementation and risk assessment of hazards due to work supervision.I This non-achievement is the result of their impact of training, which is still not effective.I Employees are still found who violate work discipline rules.I Whichi ultimately results ini ai lacki of acceptance of employee incentives. The data analysis technique used in this research is multiple linear regression analysis, which aims to see the magnitude of the influence of work disciplines training andi incentives on the performance of PTi Pamapersadai Nusantarai Easti Kalimantan employees.The research results showed that training, work disciplines, and incentives had a significant effect of 53.70%i on employees' performance. Meanwhile, I the remaining 46.30%i isi influenced by other factors including motivation, I competence, I work environment andi company culture outside this discussion.